Taking care of children with ASD by using Treatment and Education of Autistic and related Communication handicapped Children (TEACCH) : as a model an analysis of previous studies - Bouhidel, Chouaib; Bahtane, Abdelkader (Journal of Human Sciences, 2022)
The TEACCH is among the most widely used programs in the world, the main objective of this article is to increase knowledge about the importance of TEACCH program, and to reveal its advantages and the points it focuses on in improving some of the behaviors of children with ASD and those who have communication disabilities, the question was started from what is the importance of TEACCH and its role in developing the skills of people with autism and those related to communication disabilities, the descriptive approach was relied on, through a review of several previous studies, on a sample of children with ASD, the results were to prove that the TEACCH approach has the ability to provide appropriate education for children with ASD, developing functional skills, communicative functioning, motor skills , visual coordination and other important skills, as it turns out that this program is also characterized by flexibility.